Synthesis and Magnetic Characterization of Nanostructured Silicon with Bi-Metal Filling. (7th July 2017) - Rumpf, Klemens; Granitzer, Petra; Michor, Herwig; Poelt, Peter
Abstract : Bi-metal magnetic nanostructures have been deposited within porous silicon (PSi) to influence the magnetic switching behavior of the PSi/metal nanocomposite and further to enhance the energy product of the system compared to single metal nanocomposites. These nanocomposites consisting of two ferromagnetic metals have been achieved by two different routes. On the one hand both metals have been deposited alternatingly out of one solution and on the other hand the two metals have been deposited by using different metal salt solutions alternately. The latter system shows two distinct slopes of the hysteresis due to the different saturation behavior of the two types of deposited metal, whereas the system produced from one electrolyte shows no kink which indicates exchange coupling between the two metals. The comparison of these two types of samples shows that the one offering exchange coupling exhibits nearly a doubled coercivity and remanence.